Evaluasi Program Indeks Massa Tubuh dalam Meningkatkan Kebugaran Jasmani Anggota Polres Cimahi - Gilang Aditia Nugraha; Roni Mohamad Rizal; Aep Rohendi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to evaluate the effectiveness of the Body Mass Index (BMI) Program in improving the physical fitness of Polres Cimahi personnel, as mandated by Police Chief Regulation (Perkap) Number 4 of 2018 on Physical Development within the Indonesian National Police. A mixed methods approach was employed using the CIPP (Context, Input, Process, Product) evaluation model with a pre-experimental one-group pre-test post-test design involving 115 participants from January to March 2026. Quantitative data were obtained through BMI measurements and Physical Fitness Tests (UKJ), while qualitative data were gathered through in-depth interviews, structured observations, and document analysis. Results indicate: (1) Context component was effective (85.7%); strong regulatory foundation and high leadership commitment with 74.5% abnormal BMI prevalence. (2) Input component was sufficiently effective (63.6%); most instructors held national certifications, though instructor-to-participant ratio was suboptimal and indoor gym facilities were unavailable. (3) Process component was effective (72.7%); training schedule consistency was excellent and SIKJPP data recording was systematic. (4) Product component was most effective (87.5%); average BMI decreased 0.93 kg/m², total UKJ score increased 17.5%, and 75.7% of participants advanced at least one fitness category. In conclusion, the BMI Program at Polres Cimahi achieved 75.7% indicator attainment and is categorized as Effective.   Keywords: CIPP Evaluation, Body Mass Index, Physical Fitness, Polres Cimahi, Physical Fitness Test